IPD3 and IPD3L Function Redundantly in Rhizobial and Mycorrhizal Symbioses - Jin, Yue; Chen, Zixuan; Yang, Jun; Mysore, Kirankumar S.; Wen, Jiangqi; Huang, Jirong; Yu, Nan; Wang, Ertao (Frontiers in Plant Science, 2018)
Legume plants form symbiotic associations with either nitrogen-fixing bacteria or arbuscular mycorrhizal (AM) fungi, which are regulated by a set of common symbiotic signaling pathway genes. Central to the signaling pathway is the activation of the DMI3/IPD3 protein complex by Ca2+ oscillations, and the initiation of nodule organogenesis and mycorrhizal symbiosis. DMI3 is essential for rhizobial infection and nodule organogenesis; however, ipd3 mutants have been shown to be impaired only in infection thread formation but not in root nodule organogenesis in Medicago truncatula. We identified an IPD3-like (IPD3L) gene in the M. truncatula genome. A single ipd3l mutant exhibits a normal root nodule phenotype. The ipd3l/ipd3-2 double mutant is completely unable to initiate infection threads and nodule primordia. IPD3L can functionally replace IPD3 when expressed under the control of the IPD3 promoter, indicating functional redundancy between these two transcriptional regulators. We constructed a version of IPD3 that was phosphomimetic with respect to two conserved serine residues (IPD3-2D). This was sufficient to trigger root nodule organogenesis, but the increased multisite phosphorylation of IPD3 (IPD3-8D) led to low transcriptional activity, suggesting that the phosphorylation levels of IPD3 fine-tune its transcriptional activity in the root nodule symbiosis. Intriguingly, the phosphomimetic version of IPD3 triggers spontaneous root-like nodules on the roots of dmi3-1 and dmi2-1 (DMI2 is an LRR-containing receptor-like kinase gene which is required for Ca2+ spiking), but not on the roots of wild-type or ipd3l ipd3-2 plants. In addition, fully developed arbuscules were formed in the ipd3l ipd3-2 mutants but not the ccamk/dmi3-1 mutants. Collectively, our data indicate that, in addition to IPD3 and IPD3L, another new genetic component or other new phosphorylation sites of IPD3 functions downstream of DMI3 in rhizobial and mycorrhizal symbioses.